Narrating Nawal El Saadawi's Thoughts in Women at Point Zero: Psychology of Women Perspective - Anas Ahmadi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research aims to explore Nawal El Saadawi's thoughts on Women at Point Zero through psychology of women perspective which is integrated with psychoanalysis. The focus of this research refers to three things, especially in a psychological context, namely sex, crime, and death which refers to women. The research method used is qualitative-interpretive using fictional data sources. The research results show the following. Firstly, women are depicted as experiencing disclosure and sexual violence perpetrated by men (family, friends, security forces, boyfriends, pimps. The men initially communicated very well with the female character. However, in the end, they revealed sexual violence and even made Firdaus a prostitute. Second, the prostitute experiences sexual harassment and violence from her clients. Third, when a woman experiences sexual understanding, sexual violence, and making love, she takes action to resist. In this case, Firdaus kills the man who shackles her life. As a result, Firdaus received the death penalty. The death that appears in this fiction cannot be separated from the desire for death that appears in the human subconscious, whether the desire to kill other people or the desire to kill oneself. In the context of global literature, this research offers an alternative for understanding women concerning sex, crime, and death seen from a psychological perspective through literary documents.